Participation of International African Students at the University of Arkansas in Extracurricular Activities and Their Academic Outcomes - Manuel, Paulo Hadi E. (Journal of Interdisciplinary Studies in Education, 2020)
This paper examines whether there is an association between participation of the international African students at the University of Arkansas in extracurricular activities (ECAs) and their grade point average (GPA). With the increase of study abroad programs, numerous Africans at college age travel to the US to pursue their degrees. A considerable number of them get involved in extra-scholastic activities, whereas others are more concentrated on their academic programs. The researcher wanted to find whether there was a difference in GPA between those African students who were more involved in extracurricular activities and their counterparts who were least involved. Although the t-test’s results were insignificant, the qualitative results of this study may be insightful for educators and advisors who deal with international students from Africa.